BigTech and the changing structure of financial intermediation. (12th January 2020) - Frost, Jon; Gambacorta, Leonardo; Huang, Yi; Shin, Hyun Song; Zbinden, Pablo
SUMMARY: Pablo Zbinden?>We consider the drivers and implications of the growth of 'BigTech' in finance – i.e. the financial services offerings of technology companies with established presence in the market for digital services. BigTech firms often start with payments. Thereafter, some expand into the provision of credit, insurance and money management products, either directly or in cooperation with financial institution partners. Focusing on credit, we show that BigTech firms lend more in countries with less competitive banking sectors and less stringent bank regulation. Analysing the case of Argentina, we find support for the hypothesis that BigTech lenders, by acquiring a vast amount of non-traditional information, have an advantage in credit assessment relative to a traditional credit bureau. They also serve unbanked borrowers, and may have an advantage in contract enforcement. It is too early to judge the extent of BigTech's eventual advance into the provision of financial services. However, the early evidence allows us to pose pertinent questions that bear on their impact on financial stability and overall economic welfare.